2022
DOI: 10.3389/fmicb.2022.1022828
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte tropism of malarial parasites: The reticulocyte appeal

Abstract: Erythrocytes are formed from the enucleation of erythroblasts in the bone marrow, and as erythrocytes develop from immature reticulocytes into mature normocytes, they undergo extensive cellular changes through their passage in the blood. During the blood stage of the malarial parasite life cycle, the parasite sense and invade susceptible erythrocytes. However, different parasite species display varying erythrocyte tropisms (i.e., preference for either reticulocytes or normocytes). In this review, we explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 157 publications
0
6
0
1
Order By: Relevance
“…Specifically, P. yoelii prefers reticulocytes over erythrocytes by approximately 2.5 times, 41 while P. chabaudi and P. vinckei exhibit no specific tropism. 54 Given the prolonged and consistent P. yoelii infection observed in BPH mice, our findings indicate that BPH mice have a higher abundance of reticulocytes expressing erythroid lineage marker, TER119, and transferrin receptor, CD71, at basal levels. This may explain the heightened susceptibility of BPH mice to P. yoelii infections possibly attributed to a preference for reticulocytes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Specifically, P. yoelii prefers reticulocytes over erythrocytes by approximately 2.5 times, 41 while P. chabaudi and P. vinckei exhibit no specific tropism. 54 Given the prolonged and consistent P. yoelii infection observed in BPH mice, our findings indicate that BPH mice have a higher abundance of reticulocytes expressing erythroid lineage marker, TER119, and transferrin receptor, CD71, at basal levels. This may explain the heightened susceptibility of BPH mice to P. yoelii infections possibly attributed to a preference for reticulocytes.…”
Section: Discussionmentioning
confidence: 52%
“…Erythrocyte tropism is a crucial aspect of Plasmodium pathogenesis, and numerous studies have aimed to characterize merozoite preferences for erythrocytes. 51–53 For instance, P. falciparum can invade RBC at all stages, 54 while P. vivax prefers reticulocytes 54–56 ; such RBC tropism has been considered as one of the potential reasons why P. falciparum tends to be more virulent than P. vivax . Such disparity can be observed among the murine-specific Plasmodium spp .…”
Section: Discussionmentioning
confidence: 99%
“…Pk and Pf parasites can invade both reticulocytes and normocytes [57,[60][61][62]. One study evaluated reticulocyte and normocyte invasion by Pk strain A1-H.1.…”
Section: Rbc Invasionmentioning
confidence: 99%
“…The study authors mentioned that this was similar to the IC 50 of chloroquine for Pf strain 3D7, which was 6 nM at 48 h. Thus, the authors concluded that this Pk strain was chloroquine-sensitive. Chloroquine can disrupt Plasmodium parasites from degrading hemoglobin to hemozoin, leading to a buildup of heme, which is toxic for Plasmodium [62,142,143]. Because Pk is chloroquine-susceptible, it may suggest that it needs hemoglobin as a nutrient source.…”
Section: Antimalarial Medicationsmentioning
confidence: 99%
“…Neste modelo, há indução de moléculas de adesão, mas o sequestro se dá primordialmente no fígado (BRUGAT et al, 2013;STEPHENS et al, 2012;MOTA et al, 2000). Outra característica, é a estabelecida demonstração de que a infecção pode acontecer em diferentes estágios de desenvolvimento das RBCssem um tropismo muito específico por um determinado estágio como P. yoelli para reticulócitos (LEONG et al, 2022). Estes receptores são ativados por meio da interação com moléculas de PtdSer -que são expressas na superfície externa de células em processo de apoptose (LEMKE, 2013).…”
Section: Malária E Modelos Murinosunclassified